Education on the Utilization of Herbal Phytotherapy Moringa Aloifera as an Alternative Nutritional Intervention for the Prevention of Stunting in Toddlers - Muhlida, Vinilia Ihramatul; Kurniawati, Erna Yovi (Medico Insight Innovation Initiative, 2025)
Stunting remains a major chronic nutritional issue in Indonesia, including the Yogyakarta region. One preventive approach is nutrition education during the pre-marital period. Moringa oleifera is recognized as a highly nutritious local plant with potential in preventing stunting. This study employed a double-blind randomized controlled trial design involving 46 prospective brides in Yogyakarta. The intervention group received herbal phytotherapy education through an online pocketbook focused on the benefits of Moringa oleifera, while the control group received standard education from the Religious Affairs Office (KUA). Knowledge levels were assessed before and after the intervention using a structured questionnaire. There was a significant increase in knowledge scores in the intervention group (pre-test: 48.55 ± 0.93; post-test: 75.09 ± 0.95; p = 0.016), while the increase in the control group was not statistically significant. An independent t-test showed a significant difference in post-test scores between the two groups (p = 0.003). Online pocketbook-based education on Moringa oleifera herbal phytotherapy effectively increased knowledge of stunting prevention among prospective brides. This approach has strong potential as a community intervention strategy that is locally sourced, low-cost, accessible, and sustainable.